2011
DOI: 10.3201/eid1704.101679
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Pandemic (H1N1) 2009, United Kingdom, 2009–2010

Abstract: To determine clinical characteristics of patients hospitalized in the United Kingdom with pandemic (H1N1) 2009, we studied 1,520 patients in 75 National Health Service hospitals. We characterized patients who acquired influenza nosocomially during the pandemic (H1N1) 2009 outbreak. Of 30 patients, 12 (80%) of 15 adults and 14 (93%) of 15 children had serious underlying illnesses. Only 12 (57%) of 21 patients who received antiviral therapy did so within 48 hours after symptom onset, but 53% needed escalated car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
3
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 37 publications
7
32
3
4
Order By: Relevance
“…Nosocomial outbreaks of seasonal 32 and pandemic 2009 Influenza A H1N1 infection 33 can develop even in the setting of appropriate infection control measures. Seven (11%) of our patients had hospital-acquired influenza.…”
Section: Discussionmentioning
confidence: 99%
“…Nosocomial outbreaks of seasonal 32 and pandemic 2009 Influenza A H1N1 infection 33 can develop even in the setting of appropriate infection control measures. Seven (11%) of our patients had hospital-acquired influenza.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of missing data were smaller for the deaths than the survivors (0.4% vs. 36% for time to death/discharge for example), suggesting that data collection was more thorough for patients who died. 210 Poeppl 2011 198 Blumental 2011 202 Yung 2011 195 Altmann 2011 185 Enstone 2011 192 del Rosal 2011 205 Nguyen-Van-Tam 2010 186 Thompson 2011 188 Miranda-Choque 2011 197 Yokota 2011 200 Moretti 2011 208 Yang 2010 191 Mickienė 2011 Results show that when the time-dependent nature of treatment is taken into account appropriately the treatment effects change direction, although none of the results is statistically significant. Adjusting for potential confounders and imputing missing data made little difference to the results.…”
Section: Meta-analysis Of Individual Patient Datamentioning
confidence: 99%
“…10e13 However, the recent UK surveillance report indicated that the course and outcome of hospital-acquired pH1N1 can be severe both in terms of mortality and the need for escalated medical care. 14 The report suggested that more than half of the children needed intensive medical care, and one-fifth of all children with nosocomial pH1N1 died. In order to compare the clinical and epidemiological features, risk factors and outcomes of nosocomial and community-acquired pH1N1 in children, a nested caseecontrol study was conducted at six major paediatric hospitals in Australia.…”
Section: Introductionmentioning
confidence: 98%
“…10e13 A recent surveillance report from the UK described 15 cases of paediatric nosocomial influenza; to the authors' knowledge, this is the largest published report of nosocomial pH1N1 to date. 14 The literature suggests a variable presentation and outcome of hospital-acquired pH1N1 influenza. Most case series or outbreak investigations reported that paediatric nosocomial pH1N1 was generally mild, rarely needed aggressive medical care and had very low mortality.…”
Section: Introductionmentioning
confidence: 99%